Penerapan Black Box Testing Berstandar ISO 29119 Pada Aplikasi Perpustakaan Dari Repositori Github - Muhtadin, Sabilal; Jodian Saputra, Shadam; Anwar, Chairul (Journal of Information Systems and Business Technology, 2025)
The utilization of open-source software from public repositories like GitHub is increasingly prevalent in institutional system development. However, this software is often adopted without adequate quality validation processes, posing risks of functional failure in production environments. This study aims to verify the quality of a web-based "Library Information System" sourced from GitHub by implementing the international standard ISO/IEC/IEEE 29119. The methodology employed is Black Box Testing, adhering to the ISO 29119-2 dynamic test process model and ISO 29119-3 documentation structure. Testing focused on three crucial modules: library data management, user authentication, and circulation. The results indicate that out of 30 designed test cases, the system achieved a pass rate of 87%. Four major incidents were identified, including a logic flaw in book stock validation that allowed negative transactions. The implementation of the ISO 29119 standard proved effective in providing structured documentation and enhancing defect traceability.